Hydration mechanism and carbon footprint of formic acid modified coal gasification slag-based backfill material - Qiang GUO; Jixiong ZHANG; Binbin HUO; Meng LI; Nan ZHOU; Sixu LIU (Meitan kexue jishu, 2025)
The application of coal gasification slag (CGS) as backfill materials is hindered owing to its low hydration reactivity which results in insufficient strength performance of cementitious materials. This investigation applied formic acid to modify the surface of CGS in order to enhance the reactivity of CGS, and the mechanical properties, hydration mechanisms and carbon footprint of the formic acid modified CGS-based backfill material (FCM) were further investigated. The results show that after formic acid modification, part of the calcium carbonate and anorthite in CGS react with formic acid to form calcium formate, producing in-situ pores on the surface of CGS particles. The optimal formic acid dosage is 4% of CGS. At this dosage, the specific surface area of CGS particles increases from 6.32 m2/g to 9.35 m2/g, and the total pore volume increases from 0.034 2 cm3/g to 0.040 1 cm3/g. Consequently, the 3 d and 7 d compressive strengths of FCM are nearly doubled, and the cumulative hydration heat at 72 h reaches a maximum value of 81.08 J/g. However, further increasing formic acid dosage decreases the hydration activity of CGS and mechanical properties of FCM, owing to the additional reaction products covering the CGS particle surfaces, resulting in the bridging and agglomeration of CGS particles, which hindered water molecules in FCM from penetrating the particles. Additionally, the carbon life cycle assessment revealed that substituting cement with 4% formic acid modified CGS reduced the total CO2 emissions of FCM by 376.16 kg/t compared to that of the reference group, significantly lowering the carbon emissions and achieving carbon reduction targets.